Contextual Based Learning Media Development to Train Creative Thinking Skill in Primary School - Zaky Adhitya Ginanjar Sasmita; Wahono Widodo; Sifak Indana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The goal of this research is to produce learning media used context make pia cake that has category valid, practical and effective to train creativity thinking learning in primary school students. The research was conducted in 5th grade elementary school as many as 30 students. The research method used is three stages of the 4D model, namely definition, planning, development with the design of one group pretest - posttest design. This research produces 1) validity data syllabus (very valid), lesson plan (valid), teaching materials (valid), worksheet (very valid) and creative thinking skills test (valid); 2) Practicality data taken from the implementation practicality of lesson plan with good criteria; 3) The effectiveness of the device produces an N- Gain value from four components of creative thinking i.e. fluency in the high category, flexibility originality and elaboration are medium. The student's response shows delight and intrigue when learning is done using the development of contextual learning devices to train students' creative thinking skills.